To Work or Not to Work: The Hand and Embodied Wisdom of the Valiant Woman in Proverbs 31:10–31 - Ho, Shirley S. (Journal for interdisciplinary biblical studies (JIBS), 2022)
The discipline of embodied cognitive science and associated concept of intercorporeality provide the theoretical framework of our analysis of Proverbs 31:10-31. This essay fleshes out the underlying cognitive and meaning-making processes and entailments inherent in the valiant woman’s use of her hands and body as depicted in the poem. The valiant woman is contrasted with the hands and body of the sluggard fool to unveil how the activity or inactivity of the hands (and body) substantially affects the knowing of the valiant woman and the fool. Knowledge and wisdom emerged and are shaped by one’s hands and bodily interaction with the real world.